AN INVESTIGATION OF TEACHERS' PERCEPTIONS TOWARD DEEP LEARNING PEDAGOGY IN PRIMARY MATHEMATICS CLASSROOMS - Novi Andri Nurcahyono; Sani Sahara; Wily Wandari (S&Co Publishing, 2026)
This study aims to analyze elementary school teachers' perceptions of deep learning in mathematics. This qualitative study was conducted at SDN Cipinang Melayu 09 Pagi, Jakarta (May-December 2025). Fourteen elementary school teachers were selected using purposive sampling. Data were collected through questionnaires and in-depth interviews, with method triangulation employed to ensure validity. Data analysis followed qualitative research principles through reduction, categorization, presentation, and conclusion drawing. All respondents demonstrated sound understanding of deep learning as an approach focusing on mindful, meaningful, and joyful learning and acknowledged its potential benefits in enhancing concept understanding, learning motivation, and problem-solving abilities. Teacher readiness varied, with high readiness (85.7%-100%) in basic teaching skills and collaboration, and moderate readiness (78.6%-85.7%) in practical implementation. Major barriers included infrastructure limitations (71.4%), administrative burden (57.1%-64.3%), and insufficient training (78.6% had attended related training). All respondents (100%) expressed strong expectations for specialized training, adequate devices, government support, and user-friendly platforms. While teachers possessed positive perceptions and sound conceptual understanding of deep learning, effective implementation requires comprehensive systemic support including intensive training, adequate infrastructure, user-friendly platforms, policy support, reduced administrative burden, continuous mentoring, and communities of practice. With such support, deep learning possesses significant potential to transform elementary mathematics instruction.